Enabling novel functionality in heavily doped ZnO:Ga by nanostructuring: an efficient plasmonic refractive index sensor. (2nd December 2015) - Kuznetsov, Alexander S; Schäfer, Peter; John, Wilfred; Prasai, Deepak; Sadofev, Sergey; Kalusniak, Sascha
Abstract: We demonstrate a proof-of-concept refractive index sensor based on heavily doped ZnO:Ga nanostructured in a grating configuration, which supports free space excitation of propagating surface plasmons. The bulk sensitivity of the sensor of 4.9 × 10 3 nm per refractive index unit, achieved in the mid-infrared spectral range with the first grating prototype, surpasses that of the noble metal counterparts by three to four times. Sensing performance is discussed in the light of numerical simulations of the spatial profile of the near field of surface plasmon polaritons.